(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
This study examines the mediating role of transformational leadership in the relationship between project coordination, risk management, workforce competence, and the success of power transmission projects. A quantitative approach was adopted, with data gathered through structured surveys from professionals, including project managers, engineers, and contractors involved in HVDC systems, substations, and transmission lines. The findings indicate that transformational leadership significantly strengthens the impact of project coordination and risk management on project success. By fostering clear communication, motivation, and a shared vision, transformational leaders enhance the effectiveness of project teams, improve decision-making processes, and facilitate collaboration. Additionally, workforce competence was found to be positively influenced by transformational leadership, leading to better technical performance, adherence to safety standards, and timely project delivery. This study highlights the importance of leadership in shaping the outcomes of complex power transmission projects. Transformational leadership helps integrate various project elements, ensuring efficient resource utilization and minimizing risks. The study is beneficial to project managers and contractors, which shows that leadership improvement is crucial for the enhancement of project performance in power transmission projects.